Modelaje no lineal de metodología de reparación y rehabilitación de la Pila N°3 del puente sobre el Río Grande de Tárcoles en la Ruta N°34 mediante FRP - Soto-Rojas, Michael Armando (Instituto Tecnológico de Costa Rica, 2017)
The main purpose of this project is the simulation with nonlinear modeling tools of a repair methodology of a post-tensioned bridge pier by means of Fiber Reinforced Polymer Sheets (CFRP). From the detailed study carried out to the pier, a finite element model was generated, being capable of recreate the design and current condition of the pier (severe cracking pattern parallel to the element height) to later performed a pushover analysis to both, evaluating their behavior to lateral loads. The pier in its actual condition presents a reduction of 30% to withstand maximum shear loads and a 50% reduction in its deformation capacity when compared to the design condition. An additional finite element model was elaborated, based on the current condition model, to which the designed repair methodology was applied, assessing its performance when lateral loads are present. By applying growth injection and jacketing the member with one layer of CFRP partially adhered, the pier could recover its original stiffness and ductility capacity.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2017.
Keywords: Reparaciones; Estructuras; Concreto; Construcción; Puentes